Collagen-binding Streptococcus mutans tied to cerebral microbleeds and intracerebral hemorrhage. (27th September 2018) - Ihara, Masafumi; Tonomura, Shuichi; Yamamoto, Yumi; Saito, Satoshi
Genome-wide association and candidate gene studies have identified COL4A1 and COL4A2 as risk genes for intracerebral hemorrhage (ICH), suggesting that the disrupted collagen architecture could be a contributory factor in disease onset. Environmental factors that disrupt the vascular collagen architecture may therefore bring about gene–environmental interactions. Certain oral strains of Streptococcus mutans expressing Cnm, a collagen-binding protein, have been found to be responsible for ICH in a preclinical study. In support of this finding, a population-based study showed a close association between Cnm-positive Streptococcus mutans with cerebral microbleeds, a precursor of ICH, and a hospital-based study between such bacteria with cerebral microbleeds and ICH. Taken together, these findings suggest that Cnm-positive Streptococcus mutans serve as an important environmental factor in ICH.